Antarctic subglacial drilling rig: Part IV. Electrical and electronic control system. Issue 84 (11th April 2021) - Zhang, Nan; Talalay, Pavel; Liu, Jingbiao; Fan, Xiaopeng; Kong, Qingpeng; Yu, Haibin; Liu, Yunchen; Liu, Benkun; Gong, Da; Li, Xingchen; Wu, Wei; Hong, Jialin; et al.
Abstract: In many cases, the efficiency and safety of a drilling project depend on the reliability of the electrical and electronic control system, as the process progresses without visual access of the operator. The electrical and electronic system provides and regulates the power supply for the drill, collects and monitors the drill data during the whole operating process, and sends and receives the control instructions and feedback signals. The entire system is composed of the surface, borehole and software subsystems. The surface subsystem serves for operating the drilling process, transmitting the drilling and environmental data, and supplying power for the drill motor and downhole control system. The borehole subsystem is generally intended for borehole data acquisition, drill motor control, power regulation and communication. The software subsystem is designed for human–computer interaction, data processing and storage, and programming of signal acquisition and transmission of data. The control system of Antarctic subglacial drilling rig was tested during the 2018–2019 summer season near Zhongshan Station, East Antarctica, in the course of drilling to the bedrock at a depth of 198 m. It exhibited a steady and efficient performance without significant system failures.